Pengaruh Model Creative Problem Solving (CPS) Berbantuan Media Video Terhadap Keterampilan Berpikir Kreatif Siswa Sekolah Dasar - Nurjanah, Erni; Cahyadireja , Ardi; Yusuf, Ayu Nadila (Didactical Mathematics, 2025)
This study aims to determine the effect of the Creative Problem Solving (CPS) learning model assisted by video media on the creative thinking skills of fourth grade students at SD Negeri 2 Kebon Pedes. The research design used a quantitative approach with a quasi-experimental method, involving two groups, namely 31 people in the control class with conventional learning and 31 people in the experimental class with the application of the CPS model assisted by video media. The research data were obtained through creative thinking skills tests (pretest and posttest), observation. Data analysis techniques with descriptive statistical analysis to describe the data from the results of the creative thinking skills test. Normality and homogeneity tests as prerequisites for inferential analysis. Independent t-test to compare the posttest results between the experimental and control groups. Simple linear regression test to determine the magnitude of the influence of the independent variables on the dependent variable. The results of the descriptive analysis are relatively homogeneous, with a significance value of > 0.05. The independent t-test analysis produces a value of 0.000 <0.05, indicating a significant difference between the two groups. The regression coefficient result is 0.632 (p = 0.015 <0.05). The results of student activity observations show that most students have good abilities in various aspects of CPS. This confirms that the CPS model is able to encourage students to think creatively through innovative problem solving. Thus, this model is recommended to be applied in learning, especially in subjects that require the development of creative thinking skills.